Domestication causes rapid changes in heart and brain morphology in Atlantic cod (Gadus morhua) - Mayer, I; Meager, J J; Skjaeraasen, J E; Rodewald, P; Sverdrup, G; Ferno, A (Environmental Biology of Fishes, 2011)
Brain and heart development is very plastic in teleost fishes, and receptive to changes in social and environmental conditions. Domestication in salmonids has been reported to result in pronounced changes in both heart and brain morphology. In particular, a high prevalence of heart deformities has been reported in farmed salmonids, which has been linked to increased stress responsiveness that can impair survival of both farmed and escaped fish. Here we report for the first time that significant changes in heart and brain morphology occur following domestication of Atlantic cod (Gadus morhua), an emerging aquaculture species. Juvenile farmed cod developed significantly larger hearts and smaller brains, by weight, compared to their wild conspecifics. These differences occurred within the first captive generation, suggesting that they were driven largely by the strong contrast in environmental and social conditions experienced within their respective rearing environments. Changes in brain and heart morphology, as a consequence of domestication could affect the well-being and survival of Atlantic cod raised under intensive aquaculture conditions.